Molecular Characterization of Clarithromycin Resistance in Helicobacter pylori Strains - Serra Örsten; Engin Yılmaz; Yakut Akyön (Turkish Journal of Gastroenterology, 2023)
Background: The purpose of this study was to determine the antimicrobial status of stocked clinical Helicobacter pylori isolates by using antibiotic gradient test and subsequently identify the mutations that cause clarithromycin resistance by DNA sequencing. Turkey is a transition zone between Europe and Asia; therefore, we also aimed to show both continents’ mutations in Turkish isolates. Methods: One hundred forty-seven H. pylori isolates that had been stocked at −80°C between 1998 and 2008 were randomly selected and included in the study. Antibiotic susceptibility tests were performed using antibiotic gradient test for clarithromycin, amoxicillin, tetracycline, metronidazole, and levofloxacin. A polymerase chain reaction targeting the region of 23S rRNA gene domain V of H. pylori was performed and the mutations responsible for resistance against clarithromycin were defined by sequencing. Results: All of the tested isolates were found susceptible to amoxicillin and tetracycline. However, clarithromycin, metronidazole, and levofloxacin resistance were detected in 28.5% (42/147), 44.8% (66/147), and 23.1% (34/147) of the isolates, respectively. Point mutations were detected in 46 isolates (46/147, 31.2%). The majority of mutations were defined as A2143G (19/46, 41.3%), A2142G (14/46, 30.4%), and A2142C (7/46, 15.2%), respectively. T2188C, T2182C, G1949A, G1940A, and C1944T mutations were also identified in the isolates. Conclusion: In conclusion, the most common mutations associated with clarithromycin resistance in H. pylori have been identified as A2143G, A2142G, and A2142C which are the most frequently detected mutations in European countries. Same mutations and other mutations like T2182C have also been detected frequently in north-eastern countries and China. Since Turkey is a transition zone between Europe and Asia, Turkey might have strains that carry mutations found in both continents. Cite this article as: Örsten S, Yılmaz E, Akyön Y. Molecular characterization of clarithromycin resistance in Helicobacter pylori strains. Turk J Gastroenterol. 2023;34(4):427-432.